2008
DOI: 10.1007/s10384-007-0498-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical patterns of polypoidal choroidal vasculopathy in Korean patients

Abstract: The incidence of PCV in Korean exudative AMD patients was relatively high compared with that in other ethnic groups. As in other Asian patient populations, PCV occurred more commonly in men and was predominantly unilateral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 35 publications
7
85
2
2
Order By: Relevance
“…Our findings are in accordance with some studies involving Asian patients with PCV that also show a predominance of unilateral lesions [8,19,28,40]. Nevertheless, reports by Yannuzzi et al [23] (in American patients) and Ladas et al [26] (in Greek patients) show a predominance of bilateral lesions.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our findings are in accordance with some studies involving Asian patients with PCV that also show a predominance of unilateral lesions [8,19,28,40]. Nevertheless, reports by Yannuzzi et al [23] (in American patients) and Ladas et al [26] (in Greek patients) show a predominance of bilateral lesions.…”
Section: Discussionsupporting
confidence: 73%
“…Table 4 summarizes the percentages of PCV cases in several studies. The proportion of PCV in Asian patients is higher than in American and European patients with neovascular AMD [8,19,23,24,25,26,27,28]. The results of the current study show that the percentage of PCV (22.2% of patients) is similar to percentages in some reports [9,28,29] in Asian populations, but lower than the percentage reported by Maruko et al [8] and Coscas et al [24] in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCV is more prevalent in Asian and African-American populations than Caucasians, which may cause the heterogeneity in the clinical features of AMD among the races. Previous studies reported that PCV accounts for 23.0-54.7% of patients with neovascular AMD in the Japanese [11,20,30], 49% in the Taiwanese [31], 22.3-24.5% in the Chinese [32,33] and 22.2-24.6% in the Korean populations [34,35], but in only about 8-13% of Caucasians [36]. African-Americans are also known to be susceptible to PCV, although no epidemiological study for black people has been reported to date.…”
Section: Epidemiologymentioning
confidence: 99%
“…2,3 PCV is highly prevalent in Asian patients with age-related macular degeneration (AMD) and also develops in Caucasian patients. [4][5][6][7][8] Treatment with photodynamic therapy (PDT) with verteporfin (Visudyne, Novartis Pharma AG, Basel, Switzerland) can occlude the polypoidal lesions in patients with PCV. 9,10 However, the branching vascular network can remain after PDT.…”
Section: Introductionmentioning
confidence: 99%